Analysis of JSI TRIGA MARK II reactor physical parameters calculated with TRIPOLI and MCNP. (March 2015) - Henry, R.; Tiselj, I.; Snoj, L.
Abstract: New computational model of the JSI TRIGA Mark II research reactor was built for TRIPOLI computer code and compared with existing MCNP code model. The same modelling assumptions were used in order to check the differences of the mathematical models of both Monte Carlo codes. Differences between the TRIPOLI and MCNP predictions of k eff were up to 100 pcm. Further validation was performed with analyses of the normalized reaction rates and computations of kinetic parameters for various core configurations. Highlights: TRIGA Benchmark k eff calculated with the TRIPOLI code. Reaction rate profiles in TRIGA calculated with TRIPOLI code. TRIPOLI model of the JSI TRIGA was validated. TRIGA Kinetic parameters were calculated with TRIPOLI code. All results are in good agreement, largest discrepancies due to nuclear data.